Co-developmental Trajectories of Defiant/Headstrong, Irritability, and Prosocial Emotions from Preschool Age to Early Adolescence. - Ezpeleta, Lourdes; Penelo, Eva; Navarro, J. Blas; de la Osa, Núria; Trepat, Esther (Child Psychiatry & Human Development, 2022)
This study ascertains how the proposed subtypes and specifiers of oppositional defiant disorder (ODD) based on irritability and prosocial emotions co-develop and describes the clinical characteristics of the resultant classes. A sample of 488 community children was followed up from ages 3 to 12 years and assessed with categorical and dimensional measures answered by parents and teachers. Latent class growth analysis for three parallel processes [defiant/headstrong, irritability, and limited prosocial emotions (LPE)] identified a 4-class model with adequate entropy (.912) and posterior probabilities of class membership (≥.921). Class 1 (n = 38, 7.9%) was made up of children with defiant/headstrong with chronic irritability and LPE. Class 2 (n = 128, 26.3%) was comprised of children with defiant/headstrong with chronic irritability and typical prosocial emotions. Class 3 (n = 101, 20.7%) clustered children with LPE without defiant/headstrong and without irritability. Class 4 (n = 220, 45.1%) included children with the lowest scores in all the processes. The classes were distinguishable and showed different clinical characteristics through development. These findings support the validity of ICD-11 ODD subtypes based on chronic irritability and may help to guide clinicians' decision-making regarding treating oppositionality in children.